CELESTIAL MECHANICS AND HARMONY: INTELLECTUAL CURRENTS WITHIN EUROPE FROM MILANKOVIĆ TO KOSTIĆ - Dokić, Marija (Political Review, 2025)
This paper examines how the philosophical and scientific legacies of Milutin Milanković and Laza Kostić transcend national frameworks, establishing intellectual currents that affirm Serbia’s place within the broader European tradition. Their works, centered on harmony, time, and the ethical pursuit of truth, function as subtle countercurrents within Europe’s historical discourse. Through their engagement with ancient thought, they demonstrate that Serbian culture has contributed meaningfully to enduring ideas and that Serbian intellectuals have shaped the development of European philosophy and science. Before turning to their engagement with antiquity, it is essential to consider the metaphysical foundation that underlies their pursuit. This insight offers a philosophical threshold through which both Milanković and Kostić enter the realm of timeless ideas. Milanković’s scientific vision was never confined to empirical observation alone. He understood science as a metaphysical journey, a pursuit of eternal laws and cosmic harmony. This view aligns seamlessly with Kostić’s metaphysical principle, suggesting that both thinkers approached knowledge not as accumulation, but as illumination. Visionary thinkers often recognize the persistent resonance of antiquity. The aim of this study is to explore how Milanković and Kostić relate to that eternal force, one that propels their creativity and compels them to reflect ancient insights in their own distinct idioms. Whether in the history of science or the history of philosophy, their motivations unfold gradually, revealing the immortal phoenix of antiquity within their thought. That phoenix does not vanish; it merely transforms. Its name is inscribed in the layered metaphysics of classical philosophy, and its light continues to illuminate the path toward harmony, truth, and intellectual sovereignty.